Combined effects of workplace bullying and perceived organizational support on employee behaviors: does resource availability help?. Issue 6 (2nd November 2018) - Naseer, Saima; Raja, Usman; Syed, Fauzia; Bouckenooghe, Dave
ABSTRACT: Background and Objective: This research examines the detrimental effects of workplace bullying as a social stressor on employees' job performance, organizational retaliatory behaviors, and organizational citizenship behaviors and how the availability of support can reduce the negative impact of bullying. Using social exchange theory and the conservation of resources theory as theoretical frameworks, we propose that workplace bullying drains personal resources, leading to reduced job performance, low citizenship behaviors, and increased organizational retaliatory behaviors. We also propose that perceived organizational support acts as moderator, such that it reduces the detrimental effects of bullying on employee behaviors. Research Design and Methods: We tested our hypotheses in two field studies ( N = 478 and N = 395) conducted in Pakistan. Results: The results of both studies supported the assertion that workplace bullying exacerbates employees' job performance, reduces organizational citizenship behaviors and intensifies organizational retaliatory behaviors. The idea that perceived organizational support would moderate the bullying-work behavior relationships found mixed support. While perceptions of organizational support reinforced the bullying-job performance and bullying-retaliatory behaviors relationships, it did not moderate the bullying-citizenship behaviors relationship in the suggested direction. Conclusion: The findings show that workplace bullying leads to more organizational citizenship behaviors when employee's perceptions of organizational support is high.